Profile of alisporivir and its potential in the treatment of hepatitis C - Gallay PA; Lin K (Dove Medical Press, 2013)
Philippe A Gallay,1 Kai Lin21Department of Immunology and Microbial Science, The Scripps Research Institute, La Jolla, CA, 2Permeon Biologics Inc, One Kendall Square, Cambridge, MA, USAAbstract: Two classes of hepatitis C antiviral agents currently exist, ie, direct-acting antivirals and host-targeting antivirals. Direct-acting antivirals target viral proteins including NS3/NS4A protease, NS5B polymerase and NS5A protein, while host-targeting antivirals target various host proteins critical for replication of the hepatitis C virus (HCV). Alisporivir is the most advanced host-targeting antiviral in clinical development. Alisporivir blocks HCV replication by neutralizing the peptidyl-prolyl isomerase activity of the abundant host cytosolic protein, cyclophilin A. Due to its unique mechanism of antiviral action, alisporivir is pangenotypic, provides a high barrier for development of viral resistance, and does not permit cross-resistance to direct-acting antivirals. Alisporivir has an excellent pharmacokinetic and safety profile. Phase I and II clinical studies have demonstrated that alisporivir causes a dramatic reduction in viral loads in HCV-infected patients. Alisporivir was shown to be highly potent in treatment-naïve and treatment-experienced patients with genotype 1 as well as in those with genotypes 2 or 3. Low viral breakthrough rates were observed and the most frequent clinical and laboratory adverse events associated with alisporivir in combination with pegylated interferon-alpha and ribavirin were similar to those associated with pegylated interferon-alpha and ribavirin used alone. A laboratory abnormality observed in some patients receiving alisporivir is hyperbilirubinemia, which is related to transporter inhibition and not to liver toxicity. The most recent clinical results suggest that alisporivir plus other direct-acting antivirals should provide a successful treatment option for difficult-to-treat populations, such as nonresponders to prior interferon-alpha therapy and patients with cirrhosis. In conclusion, alisporivir represents an attractive candidate component of future interferon-free regimens.Keywords: alisporivir, cyclophilins, cyclophilin inhibitors, hepatitis C virus, treatment